The League of Imams and Alphas in Yorubaland, Edo, and the Delta (Rābiṭah): The Journey So Far - Akanni, Akeem A.; Ajani, Oni Idris; Busari, Saheed Abdullahi; Amina, Dawodu O. (Fakultas Syariah INSURI Ponorogo, 2024)
The southwestern region of Nigeria, primarily inhabited by the Yoruba people, has a significant Muslim population with a rich history dating back centuries. The establishment of mosques and the spread of Islam in the region was a gradual process that led to the formation of the League of Imams and Alfa in Yorubaland, Edo, and Delta (RābiTah) in 1962. This research examines the history, role, and challenges faced by the RābiTah in advance the interests of Muslims in the region. The research method used is a doctrinal approach with qualitative methods to collect and analyze information related to RābiTah. The study found that, over the years, RābiTah has achieved essential accomplishments such as becoming a respected regional Muslim league, holding annual meetings, resolving disputes, and providing awards to deserving individuals. However, the RābiTah also faced challenges, including encroachments on the Imam's authority, tribalism, political interference, and disputes among the ulama. Additionally, preferences for foreign religious rules and divisions among native clerics posed obstacles to RābiTah's goals. The implications of these findings suggest that to overcome these challenges and achieve its goals, RābiTah must prioritize unity among ulema, establish a governing body for Islamic teachings, learn from international Islamic organizations, advocate for the welfare of Imams, and increase public visibility through educational programs and outreach activities. Hopefully, these recommendations will help Rābitah strengthen its role and contribution to Muslims in the southwest region of Nigeria.